The Manifestation of the Quranic Language in the Poems of Amir Khosrow Dehlavi - Vahidi, Ahmadnoor; Heidari, Hasan; Sam-Khaniani, Mohammad Javad (LANGUAGE ART, 2020)
If we want to mention the various uses that Muslim speakers and writers - especially Iranians - have made of the Qur'an and the hadithes of the infallible, we must write a novel period of meaning and expression, because almost none of the discussions of meanings and expressions and verbal industries. And the original spirituality cannot be mentioned that the scholars of Tazi and Persian literature have not mentioned an example of the Holy Quran and the hadith of the Holy Prophet and the words of the infallible Imams. Well-known poets and writers of Persian literature have succeeded in embellishing and blessing some of their mental and intellectual leaks in the form of allusions, intimation, pastiche, and thus perpetuate those works. Undoubtedly, the secret of the immortality of the Persian language and literature is also in connection with the eternal meanings of the Qur'an. The Qur'an, this heavenly book, has added to the beauty of the poets' words and made it more beautiful and meaningful. Amir Khosrow Dehlavi (651-725 AH) is the most famous Persian poet of India, and the reflection of the Qur'an in his divan is very impressive. He also held important government positions in the court of Indian poets and emirs, and was one of those who belonged to the Chishtiyya dynasty and He served him for Nizamuddin Awliya from a young age, who was one of the famous elders of Delhi at that time. He has left many poetic and prose works in Persian in the land of India, in which in addition to showing the beauties of the Persian language, he has also addressed Quranic verses and allusions and prophetic hadithes. In this research, an attempt is made to show the reflection of Quranic verses in the poems of Amir Khosrow Dehlavi.